Handbook of Evidence-Based Practices in Intellectual and Developmental Disabilities - Singh, Nirbhay N. (Evidence-Based Practices in Behavioral Health, 2016)
This handbook presents a diverse range of effective treatment approaches for individuals with intellectual and developmental disabilities (IDD). Its triple focus on key concepts, treatment and training modalities, and evidence-based interventions for challenging behaviors of individuals with IDD provides a solid foundation for effective treatment strategies, theory-to-implementation issues, and the philosophical and moral aspects of care. Expert contributions advocate for changes in treating individuals with intellectual and developmental disabilities by emphasizing caregiver support as well as respecting and encouraging client autonomy, self-determination, and choice. With its quality-of-life approach, the handbook details practices that are person-centered and supportive as well as therapeutically sound. Topics featured in the handbook include: Functional and preference assessments for clinical decision making. Treatment modalities from cognitive behavioral therapy and pharmacotherapy to mindfulness, telehealth, and assistive technologies. Self-determination and choice as well as community living skills. Quality-of-life issues for individuals with IDD. Early intensive behavior interventions for autism spectrum disorder. Skills training for parents of children with IDD as well as staff training in positive behavior support. Evidence-based interventions for a wide range of challenging behaviors and issues. The Handbook of Evidence-Based Practices in Intellectual and Developmental Disabilities is a must-have resource for researchers, clinicians, scientist-practitioners, and graduate students in clinical psychology, social work, behavior therapy, and rehabilitation. .